2016
DOI: 10.1063/1.4941319
|View full text |Cite
|
Sign up to set email alerts
|

The electric field induced ferroelectric phase transition of AgNbO3

Abstract: Coexistence of two phases of AgNbO3 is shown to explain the experimentally observed polarization–electric field hysteresis loop better than either phase in isolation, based on detailed first-principles calculations of the structural changes and stabilities of different phases of this compound. Calculations confirm a ferroelectric phase transition, whereby the symmetry of the AgNbO3 crystal switches from antiferroelectric Pbcm to ferroelectric Pmc21, under an electric field of 9 MV/cm. The calculated spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…DFT calculations of AgNbO 3 under an applied electric field showed that a fully FE structure, also belonging to space group Pmc2 1 , and which we refer to as the F phase, becomes stable, with a theoretical polarization value of 61 μC/cm 2 , in good agreement with the measured polarization under an applied electric field of 52 μC/cm 2 [19]. The F-Pmc2 1 structure is compared with M1-Pbcm and M1-Pmc2 1 structures in Fig.…”
Section: Introductionsupporting
confidence: 74%
“…DFT calculations of AgNbO 3 under an applied electric field showed that a fully FE structure, also belonging to space group Pmc2 1 , and which we refer to as the F phase, becomes stable, with a theoretical polarization value of 61 μC/cm 2 , in good agreement with the measured polarization under an applied electric field of 52 μC/cm 2 [19]. The F-Pmc2 1 structure is compared with M1-Pbcm and M1-Pmc2 1 structures in Fig.…”
Section: Introductionsupporting
confidence: 74%
“…[13][14][15] However, the existence of polar regions at room temperature was ascertained by detailed diffraction studies has been reported more recently. 12,16,17 The coexistence of antiferroelectric (AFE) and FE states in AgNbO 3 yields a complicated sequence of electric field-induced events, as observed in the current-polarization-electric field hysteresis loops previously reported. 12 It was found that bismuth niobate, BiNb 3 O 9, crystalizes as an A-site deficient metastable perovskite super-cell structure (i.e., Bi 1/3 NbO 3 ).…”
Section: Introductionmentioning
confidence: 68%
“…They exhibit a number of phases [14,15] associated with lattice instabilities of the reference cubic phase [16]. The transitions between phases are commonly driven by temperature [14,15], pressure [17][18][19], or static electric fields [20]. Here, we demonstrate that light can also act as a knob to control the crystal symmetry.…”
mentioning
confidence: 78%